De/Stabilizing Heterosexuality in the Pardoner’s Tale - Dhouib, Mohamed Karim (International Journal of Language and Literary Studies, 2021)
The paper sets out to argue that the Pardoner’s atypical sexuality is subversive of the medieval gender matrix and that his challenge to heteronormativity is ultimately encompassed and disarmed. Chaucer presents the Pardoner as a genderly ambiguous Other who does not fit the compulsory pattern of the two biological sexes. In its pronounced otherness and difference, his queer body disrupts the medieval normative order. Paradoxically, however, his difference re-inscribes that very order and reinforces the institutional status quo. His transgressive potential is met by containment and heterosexual hegemony is eventually re-established and re-affirmed.